Application Of The Defense Style Questionnaire (DSQ) Model Of Self Defense Mechanism In Post Stroke Patients - Sunaringtyas, Widyasih; Sulistyorini, Ariani; Fernanda, Feri (Chakra Brahmanda Lentera Institute, 2023)
Background: Post-stroke patients experience changes in physical function so that they need self-defense mechanisms in order to adapt to their conditions. The self-defense mechanism model that a person uses appears when a person faces a reality that causes fear, anxiety, and insecurity. The purpose of this study was to determine the model of self-defense mechanisms in post-stroke patients in the working area of the UPTD Bendo Health Center, Pare District, Kediri Regency. Methods: The research design is descriptive, the research population is 56 people and the research sample is 49 respondents using a purposive sampling technique. The research was conducted on March 20 - April 20 2023. The research variables were models of self-defense mechanisms in post-stroke patients. The research instrument used a defense style questionnaire. Results: The results showed that 22.40% used the mature, neurotic, immature model, 10.2% of the respondents used mature and neurotic, 14.3% of the respondents used the mature, immature model, 8.20% of the respondents used neurotic, immature, 16.3% respondents used the mature model, 8.20% used immature and 8.20% used neurotic and 12.2 respondents did not use the self-defense mechanism model. Conclusion: The self-defense mechanism model used by respondents was influenced by several factors including age, gender, work history, and family support, information. Models of self-defense mechanisms in post-stroke can be used simultaneously or alternately, useful for facilitating physical adaptation for post-stroke patients